If f(x) = x + 4 and g(x) = 2x - 3, find (g - f)(2).

If f(x) = x + 4 and g(x) = 2x - 3, find (g - f)(2).

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

\( (g-f)(2) = g(2) - f(2)\)
Can you do the next step?

No .. im sorry i really dont know this . @OneMathCat

\(g(x) = 2x - 3\)
\(g(2) = 2\cdot 2 - 3\)
Do you see the pattern?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.